Does Religious Holiday Allowance Policy during Covid-19 Provide Legal Certainty? - Aries Harianto (Sriwijaya Law Review)
The Circular Letter of the Minister of Manpower No. M/6/HI.00.01/V/2020 concerning the Implementation of Religious Holiday Allowance Payment (THR) of 2020 in Companies during Covid-19 Pandemic is a regulation expected to complete THR payment problems in this Pandemic situation. However, normatively, this regulation raises new legal issues. This regulation's provisions contradict the principle of legal certainty because it contradicts the laws and regulations above it. Under the juridical normative type of research, the results of this research found the emergence of legal consequences due to industrial relations disputes for employment relations actors if the agreement on THR Payment is not achieved. This research has also found that the Minister Circular Letter on THR Payment basically contradicted the principle of legal certainty because the status does not belong to the statutory regulations, meaning that it has no force to be applied as statutory regulations do. Based on the Statutory regulation, the minister Circular Letter's legal status only applies to internal institutions which issue and belongs to technical and administrative arrangements. Thus, legal action as research result recommended to the government is revoking the minister's circular letter on THR Payment.